A unified filter for simultaneous input and state estimation of linear discrete-time stochastic systems. (January 2016) - Yong, Sze Zheng; Zhu, Minghui; Frazzoli, Emilio
Abstract: In this paper, we present a unified optimal and exponentially stable filter for linear discrete-time stochastic systems that simultaneously estimates the states and unknown inputs in an unbiased minimum-variance sense, without making any assumptions on the direct feedthrough matrix. We also provide the connection between the stability of the estimator and a system property known as strong detectability, and discuss the global optimality of the proposed filter. Finally, an illustrative example is given to demonstrate the performance of the unified unbiased minimum-variance filter.